Global legume diversity assessment: Concepts, key indicators, and strategies. Issue 2 (27th December 2018) - Yahara, Tetsukazu; Javadi, Firouzeh; Onoda, Yusuke; de Queiroz, Luciano Paganucci; Faith, Daniel P.; Prado, Darién E.; Akasaka, Munemitsu; Kadoya, Taku; Ishihama, Fumiko; Davies, Stuart; Slik, J.W. Ferry; Yi, Tingshuang; et al.
Abstract: While many plant species are considered threatened under anthropogenic pressure, it remains uncertain how rapidly we are losing plant species diversity. To fill this gap, we propose a Global Legume Diversity Assessment (GLDA) as the first step of a global plant diversity assessment. Here we describe the concept of GLDA and its feasibility by reviewing relevant approaches and data availability. We conclude that Fabaceae is a good proxy for overall angiosperm diversity in many habitats and that much relevant data for GLDA are available. As indicators of states, we propose comparison of species richness with phylogenetic and functional diversity to obtain an integrated picture of diversity. As indicators of trends, species loss rate and extinction risks should be assessed. Specimen records and plot data provide key resources for assessing legume diversity at a global scale, and distribution modeling based on these records provide key methods for assessing states and trends of legume diversity. GLDA has started in Asia, and we call for a truly global legume diversity assessment by wider geographic collaborations among various scientists.